2011
DOI: 10.1002/hbm.21307
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visual functioning in autism: An ALE meta‐analysis

Abstract: Autistics often exhibit enhanced perceptual abilities when engaged in visual search, visual discrimination, and embedded figure detection. In similar fashion, while performing a range of perceptual or cognitive tasks, autistics display stronger physiological engagement of the visual system than do non-autistics. To account for these findings, the Enhanced Perceptual Functioning Model proposes that enhanced autistic performance in basic perceptual tasks results from stronger engagement of sensory processing mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
191
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(226 citation statements)
references
References 164 publications
(219 reference statements)
29
191
0
6
Order By: Relevance
“…Although not part of the core ASD symptoms, enhanced low‐level visual processing abilities are widely acknowledged (see Dakin & Frith, 2005 for a review), and translate into increased occipital activation upon various types of visual stimulation (Samson, Mottron, Soulieres, & Zeffiro, 2012), of which stronger occipital ISFC transients as seen here could be a consequence. Interestingly, it has recently been suggested that increased visual responsiveness to low‐level features, as reported in this study, may arise due to a larger noise in the primary visual system (Simmons et al, 2009; Lawson, Rees, & Friston, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Although not part of the core ASD symptoms, enhanced low‐level visual processing abilities are widely acknowledged (see Dakin & Frith, 2005 for a review), and translate into increased occipital activation upon various types of visual stimulation (Samson, Mottron, Soulieres, & Zeffiro, 2012), of which stronger occipital ISFC transients as seen here could be a consequence. Interestingly, it has recently been suggested that increased visual responsiveness to low‐level features, as reported in this study, may arise due to a larger noise in the primary visual system (Simmons et al, 2009; Lawson, Rees, & Friston, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Visual processing involves the striate cortex within the calcarine fissure, and the surrounding cortex, including the cuneus, the caudal portion of the precuneus, and the lingual gyrus. Findings of abnormalities in visual cortex in ASD are common (Barbeau et al, 2015;Samson et al, 2012;Philip et al, 2012;Green et al, 2013). Auditory processing involves Heschl's gyrus and the surrounding cortex within the superior temporal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, "sensory hypersensitivity" (Baron-Cohen et al, 2009) has been detected in different modalities (vision, audition and touch) in ASC individuals (Bonnel et al, 2003;Bertone et al, 2005;O'Riordan and Passetti, 2006;Tommerdahl et al, 2007;Heaton et al, 2008;Simmons, 2009). Further, increased brain activation in primary, as well as more associative, areas connected with visual processing has been found in a wide range of different cognitive tasks, as reported by a recent meta-analysis (Samson et al, 2012). Sensory hypersensitivity in the modality of the concurrent has also been detected in synaesthetes ) and enhanced visual evoked potentials unrelated to synaesthetic sensation have been found in synaesthetes as well (Barnett et al, 2008a,b).…”
Section: Discussion Relation Between Synesthesia and Ascmentioning
confidence: 84%
“…Increased activation in associative cortex regions involved in higher order sensory processing has been found in ASC individuals in the visual domain (Samson et al, 2012), while increased functional connectivity between frontal areas (Noonan et al, 2009) and between posterior cingulate and medial temporal cortex (Monk et al, 2009) has been found using fMRI. In synesthesia, the parietal cortex especially has been found to be hyperactivated in different types of synesthesia and this region has also been found to be more strongly connected to the sensory areas involved in inducer-and concurrent processing , supporting the idea of top-down modulation of sensory areas by this higher-order associative region.…”
Section: Discussion Relation Between Synesthesia and Ascmentioning
confidence: 99%